Foreign exchange crises : an essay in economic pathology - Einzig, Paul. (London ; New York : Macmillan ; St Martin's Press, 1970)
This book examined the issue of foreign exchange crises with emphasis on direct causes of selling pressure on an exchange and the indirect causes as well. Also it examines the various measures adopted or proposed to meet foreign exchange crises.
Includes index
Bibliography: p. 200-201.
usc 25/05/18
Loans
Keywords: Foreign exchange